Ixazomib-Thalidomide-Dexamethasone for induction therapy followed by Ixazomib maintenance treatment in patients with relapsed/refractory multiple myeloma - Ludwig, Heinz; Poenisch, Wolfram; Knop, Stefan; Egle, Alexander; Schreder, Martin; Lechner, Daniel; Hajek, Roman; Gunsilius, Eberhard; Krenosz, Karl Jochen; Petzer, Andreas; Weisel, Katja; Niederwieser, Dietger; et al. (British journal of cancer, 2019)
BACKGROUND: Ixazomib-revlimid-dexamethason showed significant activity in relapsed/refractory multiple myeloma (RRMM). Here, we evaluate ixazomib in combination with thalidomide and dexamethasone for induction treatment followed by ixazomib maintenance therapy in RRMM patients. METHODS: Ninety patients have been included. Ixazomib-thalidomide-dexamethasone (4 mg, day 1, 8, 15; 100 mg daily; and 40 mg weekly) was scheduled for eight cycles followed by maintenance with ixazomib for one year. RESULTS: The overall response rate was 51.1%, 23.3% achieved CR or VGPR and 10% MR resulting in a clinical benefit rate of 61.1%. In patients completing ≥2 cycles, the rates were 60.5%, 27.6% and 68.4%, respectively. Median progression-free survival (PFS) was 8.5 months in all, and 9.4 months in those completing ≥2 cycles. Response rates, PFS and overall survival (OS) were similar in patients with and without t(4;14) and/or del(17p), but PFS and OS was significantly shorter in patients with gain of 1q21. Multivariate regression analysis revealed gain of 1q21 as the most important factor associated with OS. Ixazomib maintenance resulted in an upgrade in the depth of response in 12.4% of patients. Grade 3/4 toxicities were relatively rare. CONCLUSIONS: Ixazomib-thalidomide-dexamethasone followed by ixazomib maintenance therapy is active and well tolerated in patients with RRMM. TRIAL REGISTRATION NUMBER: NCT02410694.
Keywords: dexamethason; glycin; Maintenance Chemotherapy; Thalidomide; lidé; Middle Aged; Adult; thalidomid; míra přežití; Female; Multiple Myeloma; Dexamethasone; Survival Rate; indukční chemoterapie; Humans; protokoly protinádorové kombinované chemoterapie; Progression-Free Survival; Induction Chemotherapy; doba přežití bez progrese choroby; lidé středního věku; Glycine; sloučeniny boru; mužské pohlaví; mnohočetný myelom; ženské pohlaví; udržovací chemoterapie; Aged, 80 and over; senioři nad 80 let; Male; Aged; dospělí; Antineoplastic Combined Chemotherapy Protocols; Boron Compounds; senioři